SP4.2.12 The impact of COVID 19 on colorectal cancer diagnosis and surgical oncological provision; A national perspective. (28th October 2021) - Donlon, Noel; Nugent, Tim; Irwin, Shane; Ramjit, SInead; Davern, Maria; Mealy, Ken
Abstract: Introduction: The COVID-19 pandemic has interfered with many aspects of cancer management, including delayed diagnoses, stalled screening programmes, limiting treatment and clinical trials. Colorectal cancer is the second commonest cause of cancer death in Ireland. The objective of the current study is to assess the impact of this pandemic on colorectal cancer diagnoses and surgery, at a national level. Methods: Data on endoscopy, emergency and elective colorectal operations nationally in Ireland over a three year period (2018-2020) were obtained from the National Quality Assurance Improvement System. Data relating to cancer surgery only were included and patient demographics, type of surgery (open/laparoscopic), length of stay (LOS), mortality, admission to critical care and re-admission rates were collected and analysed. Results: 31.33% less cancers have been diagnosed between March and November 2020 inclusive when compared to the same period over the past two years with 22% less rectal cancers identified. There has been a 34% reduction in colorectal cancer surgeries over the same period with a reduction of 42% at the initial wave during the period March-May and of concern, this trend has continued. Laparoscopic right hemicolectomies have reduced by 41%, anterior resections have reduced by 51% with no change in the number of temporary ileostomies over the three year period. Conclusion: The impact of COVID-19 on colorectal cancer surgery nationally has been profound. The reduction in diagnoses and cancer surgery is concerning and may result in increased late or incurable stage disease as a consequence of late presentation and diagnosis.